2014
DOI: 10.3109/07420528.2014.963198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adrenalectomy on daily gene expression rhythms in the rat suprachiasmatic and paraventricular hypothalamic nuclei and in white adipose tissue

Abstract: It is assumed that in mammals the circadian rhythms of peripheral clocks are synchronized to the environment via neural, humoral and/or behavioral outputs of the central pacemaker in the suprachiasmatic nucleus of the hypothalamus (SCN). With regard to the humoral outputs, the daily rhythm of the adrenal hormone corticosterone is considered as an important candidate. To examine whether adrenal hormones are necessary for the maintenance of daily rhythms in gene expression in white adipose tissue (WAT), we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 89 publications
8
52
0
Order By: Relevance
“…In the present study we showed that the daily rhythm of clock gene expression in the liver is still intact under 6-meals-a-day feeding conditions, after adrenalectomy, after total hepatic denervation or after total hepatic denervation with adrenalectomy or 6-meals-a-day feeding schedule. These results are similar to previous findings in liver (Cailotto et al 2005;Oishi et al 2005;Pezuk et al 2012;Sujino et al 2012), epididymal white adipose tissue (eWAT) (Su et al 2014(Su et al , 2015, kidney (Pezuk et al 2012;Sujino et al 2012), salivary gland (Pezuk et al 2012) and lung (Pezuk et al 2012). Together these findings demonstrate that feeding rhythm, adrenal hormones (in particular corticosterone) and neuronal inputs are not indispensable for synchronized daily clock gene rhythms.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we showed that the daily rhythm of clock gene expression in the liver is still intact under 6-meals-a-day feeding conditions, after adrenalectomy, after total hepatic denervation or after total hepatic denervation with adrenalectomy or 6-meals-a-day feeding schedule. These results are similar to previous findings in liver (Cailotto et al 2005;Oishi et al 2005;Pezuk et al 2012;Sujino et al 2012), epididymal white adipose tissue (eWAT) (Su et al 2014(Su et al , 2015, kidney (Pezuk et al 2012;Sujino et al 2012), salivary gland (Pezuk et al 2012) and lung (Pezuk et al 2012). Together these findings demonstrate that feeding rhythm, adrenal hormones (in particular corticosterone) and neuronal inputs are not indispensable for synchronized daily clock gene rhythms.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies suggest that GC also directly affect clock gene expression in metabolically active tissues, such as liver and kidney, whereas they can trigger rhythmic gene expression in the liver of SCN-lesioned animals (Balsalobre et al, 2000;Oishi et al, 2005;Reddy et al, 2007). By contrast, in the white adipose tissue and liver, adrenalectomy abolishes many daily rhythms in metabolic/adipokine gene expression, but not clock gene expression (Oishi et al, 2005;Su et al, 2014). Moreover, besides clock mechanisms, the GC rhythm is profoundly affected by stress and stressful events occurring during the daily trough of plasma GC (i.e., late night and morning in nocturnal species) will therefore mask the endogenous rhythm of GC.…”
Section: Glucocorticoid Rhythmmentioning
confidence: 99%
“…Sham-ADX was performed using the same approach, with only localization of the adrenals, leaving the glands intact. ADX rats were maintained on 0.9% NaCl to correct the aldosterone insufficiency throughout the 10 days following the operation (Su et al 2015).…”
Section: Adrenalectomymentioning
confidence: 99%